Athletic talent: Methodological foundation - Issurin, V. (EWF Scientific Magazine, 2018)
Athletic Talent is a complex, multifaceted phenomenon that is widely considered from methodological, biological, philosophical and social positions. The available literature embraces a large body of findings and evidence that can be clustered into three basic branches: methodological foundation, hereditary and biological premises, data and evidence from sport psychology. The methodological foundation can be considered the basic background of general comprehension of the problem and fulfillment of various scientific and practical projects directed toward recognition, identification and promotion of talented individuals. Of course, the biological and psychological premises are major contributors of athletic talent and they will be considered later in the article. Athletic Talent is definitely one of the most intriguing and widely discussed issues in sport science and practice. Although there has been interest in this problem since many decades ago, when high-performance sport became a reality of social, cultural, and political life, the systematic studies of Athletic Talent have a relatively short history. In fact, the serious investigations of Athletic Talent were only been initiated in the early 1970's in Eastern European countries. One of the most efficient, hierarchical systems for talent identification and development was elaborated on and fulfilled in East Germany (former GDR). The serious, methodological input to theoretical and evaluation background of TI and TDV was done in the USSR. A number of prospective studies were also conducted in Western European countries and in the USA. Since the early 1990's, experience from former communist countries became available for the community of international training experts and analysts. As a result, a number of "talent search" projects were successfully realized in Australia, Canada, Great Britain, the USA, the Netherlands, Belgium, Germany, and Switzerland. The tremendous progression of Chinese Olympic athletes was, to a great extent, conditioned by the application of a strictly structured system of talent search and nurturing from the school level until national Olympic centers and national teams. During the latest decades, a large number of studies have been conducted to verify batteries of relevant estimates for evaluation of giftedness of athletes in different sports. Employment of various tests such as motor fitness, physical skills, body build, physiological, and psychological abilities in different combinations allowed recognition of more prospective candidates with an accuracy that varies between 67-95%. However, this accuracy drastically decreases in attempts to predict talent from a long-term perspective. Summarizing the evidence from prospective, long-lasting projects and practically oriented studies conducted for the needs of certain sports, a number of relevant issues can be highlighted, namely: - the commonly accepted approach presupposes the division of longterm preparation into a number of stages where various age and sport-specific tasks be solved and young athletes overcome appropriate phases of their giftedness and talent evaluation; - the objective difficulties in TI are associated with differences in the rate of maturation and unevenness of biological and sport-specific development of young prospects; - serious restrictions of early evaluation of giftedness and talent are associated with the lack of psychological measures and insufficient attention to personality traits that, to a great extent, determine the achievement of exceptional performance; - the TI in team sports needs more sensitive tests for prediction of successful game activity; such an item as fatigue tolerance was not taken into account by training experts and analysts.